EDITORIAL: Eco-Sanctuaries Amid Green Sacrifice - Attumkal, Mathew (Journal of Dharma, 2025)
The twenty-first century confronts humanity with a profound paradox. Even as global awareness of the sacredness of nature deepens across cultures and faith traditions, the very ecosystems we revere are increasingly imperilled by industrial expansion, climate instability and development-driven interventions. This tension—between biophilia, humanity’s innate affinity for life, and theophilia, its reverence for the divine—gives rise to what may be called a spiritual hybrid dilemma. At this crossroads stand eco-sanctuaries: spaces of reverence and protection that are simultaneously threatened by narratives of sacrifice invoked in the name of progress. Historically, eco-sanctuaries such as sacred groves, rivers, wetlands, forests, mountains and revered landscapes, have embodied a harmonious convergence of spirituality, culture and ecology. Across civilizations, human communities have intuitively recognized that certain places possess intrinsic value beyond material utility. In India, sacred groves have preserved endemic species, stabilized soil and water systems and functioned as ecological corridors within human-dominated landscapes. Rivers such as the Ganges, the Jordan and the Nile were ritually protected through religious observance, sustaining both ecological processes and social cohesion. In Africa, sacred forests and cultural taboos have long safeguarded biodiversity, while in East Asia, temple lands and mountain sanctuaries have quietly conserved habitats for centuries. These examples reveal an enduring truth: conservation has never been driven solely by policy or economics. Moral imagination and spiritual worldviews have historically shaped ecological behaviour. Sacred spaces function as living laboratories where human values, ethical commitments and empirical ecology intersect, offering generative models of sustainable land management and responsible stewardship